Who is responsible for metabolic screening for mental health clients taking antipsychotic medications? - Ward, T.; Wynaden, Dianne; Heslop, K. (Wiley-Blackwell Publishing Asia, 2017)
Metabolic syndrome is common in mental health consumer populations, and is linked to cardiovascular disease, stroke and diabetes. Metabolic screening is a way of recognising consumers who are at risk of developing metabolic syndrome but internationally screening rates remain low. A retrospective audit was completed at one Australian public mental health service on the case files of 100 randomly selected consumers to determine nurses level of compliance with metabolic screening policies over a 12 month period. Consumers included in the review were prescribed antipsychotic medications for at least 12 months and had their care in the community coordinated by mental health nurses. Data were entered into an Excel spreadsheet for analysis. Low levels of metabolic screening were identified and these levels decreased over the 12 months under review. No consumers had metabolic screening that recorded all parameters at three monthly intervals over the 12 month period. Only one consumer had every metabolic parameter recorded on the physical health screen tool at baseline assessment. The findings demonstrated that while there is increased awareness of co-morbid physical health issues in this consumer population, the translation of guidelines and policy directives to clinical practice to address this disparity remains low. Improving physical health outcomes is the responsibility of all health professionals, particularly doctors who prescribe and nurses who administer antipsychotic medications regularly to mental health consumers. Moreover, nurses are well placed to demonstrate leadership in reducing the rate of metabolic syndrome through the delivery of holistic care that includes effective screening programs.